Makna Kesedihan Dalam Lagu Yozora, Lemon dan Aishiteru No Ni Aisenai - Khansa Nur Azkia; Budi Rukhyana; Paramita Winny Hapsari (Universitas Pakuan, 2021)
ABSTRACT: This study analyzes the physical elements, mental elements and the meaning of sadness in three different songs. This analysis uses descriptive analysis method, which is one type of method used to analyze and describe it. The data collection technique used to analyze is library research, which is a technique for collecting data by means of literature, as well as looking for a number of references and data from the internet related to research. The purpose of this study is to find out the true meaning of sadness in the songs of Yozora, Lemon, and Aishiteru no ni Aisenai. The results of the data analysis show what the meaning of sadness in the songs of Yozora, Lemon, and Aishiteru no ni Aisenai is through Albertine's perspective.